2021
DOI: 10.1111/1365-2745.13601
|View full text |Cite
|
Sign up to set email alerts
|

Functional diversity and trait composition of vascular plant and Sphagnum moss communities during peatland succession across land uplift regions

Abstract: Most of the carbon accumulated into peatlands is derived from Sphagnum mosses. During peatland development, the relative share of vascular plants and Sphagnum mosses in the plant community changes, which impacts ecosystem functions. Little is known on the successional development of functional plant traits or functional diversity in peatlands, although this could be a key for understanding the mechanisms behind peatland resistance to climate change. Here we aim to assess how functionality of successive plant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 145 publications
(151 reference statements)
1
38
0
Order By: Relevance
“…Among Sphagnum traits, we predicted that (d) Sphagnum metabolites have a stronger effect in shaping microbial properties than anatomical and morphological traits, since metabolites are released into Sphagnum surroundings and can directly influence microbial community composition and/or microbial traits. Finally, as Sphagnum traits do not exclusively vary with climatic and edaphic conditions (Sytiuk et al, 2020), but also according to phylogeny (Laine et al, 2021), we hypothesized that (e) Sphagnum phylogeny is an important determinants of microbial properties, in addition to climatic and edaphic conditions and Sphagnum traits.…”
Section: Synthesismentioning
confidence: 99%
“…Among Sphagnum traits, we predicted that (d) Sphagnum metabolites have a stronger effect in shaping microbial properties than anatomical and morphological traits, since metabolites are released into Sphagnum surroundings and can directly influence microbial community composition and/or microbial traits. Finally, as Sphagnum traits do not exclusively vary with climatic and edaphic conditions (Sytiuk et al, 2020), but also according to phylogeny (Laine et al, 2021), we hypothesized that (e) Sphagnum phylogeny is an important determinants of microbial properties, in addition to climatic and edaphic conditions and Sphagnum traits.…”
Section: Synthesismentioning
confidence: 99%
“…Peat soils characterized by high mineral nutrient, medium pH, low soil oxygen content and high soil water content promote plant communities dominated by specialized vascular plants such as wetland sedges (Carex spp.) and some forbs species (Robroek et al, 2015;Laine et al, 2021). In contrast, peat soils characterized by low mineral nutrient content, low pH, low soil oxygen content and high soil water content enhance plant communities dominated by peat mosses (Sphagnum spp.)…”
Section: Soil Oxygen Soil Ph Nutrient Contents and Litterfall Qualitymentioning
confidence: 99%
“…During this phase vegetation cover is fully recovered and plant community is characterized by typical peatlands genera such as Sphagnum, Eriophorum and Carex. Final composition will likely be a function of nutrient content and pH (Laine et al, 2021). There is evidence of effective restoration of ecological properties through rewetting (Menberu et al, 2016;Alderson et al, 2019;Ahmad et al, 2020;Purre et al, 2020), but this process might require up to 30 years and for some systems might not be possible due to changes associated with long term drainage (Holden et al, 2004;Kreyling et al, 2021).…”
Section: Restoration Phasesmentioning
confidence: 99%
“…Recent publications focused on bryophyte functional traits have considerably increased our knowledge regarding the relationship between the environment and bryophyte functional traits [ 25 , 26 , 27 , 28 , 29 ]. In particular, some of these studies identified water chemistry (e.g., pH, dissolved nutrients, and heavy metals) as an important determinant of moss traits and growth forms [ 2 , 25 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent publications focused on bryophyte functional traits have considerably increased our knowledge regarding the relationship between the environment and bryophyte functional traits [ 25 , 26 , 27 , 28 , 29 ]. In particular, some of these studies identified water chemistry (e.g., pH, dissolved nutrients, and heavy metals) as an important determinant of moss traits and growth forms [ 2 , 25 , 28 ]. Other studies, focused on how several traits are related to each other, made very relevant contributions in order to emulate the leaf economic spectrum described for vascular plants [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%